An investigation on the influence of various biochemical tenderness factors on eight different bovine muscles - Hammond, Peang Abigail (Kansas State University, 2021)
Tenderness is defined as the amount of force required to bite through a piece of meat. Despite its simple definition, three factors underlie the complexity of tenderness: the actomyosin, the background, and the bulk density or lubrication effects. However, past studies concluded that no single tenderness component could predict beef tenderness for all cuts. Therefore, this study's objective was to understand the relationships of biochemical tenderness components and the perception of overall tenderness of eight muscles from the forequarter and the hindquarter of beef carcasses. Longissimus thoracis (LT), pectoralis profundus (PP), supraspinatus (SS), triceps brachii (TB), gluteus medius (GM), rectus abdominus (RA), rectus femoris (RF), and semitendinosus (ST) were collected from 10 UDSA upper 2/3 choice beef carcasses and assigned to a two or 21 day aging period (n = 160). Troponin-T (TNT) degradation, desmin degradation, sarcomere length, muscle fiber cross sectional area (CSA) and diameter, collagen content, mature collagen crosslink density, intramuscular lipid content, pH, trained panel analyses, and Warner-Bratzler Shear Force (WBSF) were measured. A Pearson correlation analysis was conducted to determine the relationship between each tenderness contributor measured in this study and the overall tenderness evaluated by the trained panelist and WBSF. In addition, multivariate regression models were constructed to confirm this relationship. The results showed that muscle anatomical locations and physiological functions driven by muscle fiber types may explain some of the biochemical and/or tenderness differences found in this study. The correlation analysis showed that all of the biochemical measurements conducted (except for pH) in this study played a small but important role as an overall tenderness predictor (P < 0.01); however, each muscle has a specific tenderness factor(s) that contributed to the overall tenderness evaluated by trained panelists. For instance, tenderness for LT, TB, GM, RA, and ST may be influenced by proteolytic degradation, while the collagen characteristics may primarily influence tenderness for PP. Also, lipid content has a significant influence on GM tenderness. Increasing the knowledge base on the various tenderness components' level of contribution will allow end-users to develop specific tenderness management strategies to ensure consistent tenderness in beef products.
Keywords: Beef; Tenderness; Trained panel; Proteolysis; Collagen; Lipid